The Engineer in America : (University of Chicago Press, 1991)
With some two million practitioners, engineers form one of America's largest professional groups; indeed, it is the single largest occupation of American males today. The rise of this profession and its place in American society provide the focus for this anthology. Spanning two centuries and the various subdisciplines of the field, these essays demonstrate the paradoxical role engineers have played in building (although usually not controlling) the infrastructure on which America's prosperity is based. This collection of seventeen essays traces the rise of the engineering profession and its evolving contribution to the development of America's material and economic success.